2006
DOI: 10.1007/s10347-006-0090-0
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of common reef-building coral genera Acropora, Pocillopora, Goniastrea and Porites: constraints on spatial resolution in geochemical sampling

Abstract: Scleractinian corals are increasingly used as recorders of modern and paleoclimates. The microstructure of four common reef-building coral genera is documented here: Acropora, Pocillopora, Goniastrea, and Porites. This study highlights the complexity and spatial variability of skeletal growth in different coral genera and suggests that a single growth model is too generalized to allow the accurate depiction of the variability observed in the four genera studied. New models must be introduced in order for coral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 58 publications
8
94
0
Order By: Relevance
“…It was shown that the two ultrastructural components of coral skeleton i.e., COC and fibers, are characterized by different nanostructural organization and geochemical signatures (Benzerara et al, 2011;Cuif and Dauphin, 2005;Meibom et al, 2007;Nothdurft and Webb, 2007;Perrin, 2003;Stolarski and Mazur, 2005). Considering geochemical signatures, Meibom et al (2007) reported a depletion of Sr/Ca in COCs compared to fibers in Porites sp..…”
Section: Origin Of the Intra-skeletal Calcite: Biogenic Vs Early Diamentioning
confidence: 99%
“…It was shown that the two ultrastructural components of coral skeleton i.e., COC and fibers, are characterized by different nanostructural organization and geochemical signatures (Benzerara et al, 2011;Cuif and Dauphin, 2005;Meibom et al, 2007;Nothdurft and Webb, 2007;Perrin, 2003;Stolarski and Mazur, 2005). Considering geochemical signatures, Meibom et al (2007) reported a depletion of Sr/Ca in COCs compared to fibers in Porites sp..…”
Section: Origin Of the Intra-skeletal Calcite: Biogenic Vs Early Diamentioning
confidence: 99%
“…This study sampled at 0.70 mm (approximately monthly) intervals using a 1.4 mm drill bit and each sample area contains $1.47 mm 2 of coral skeletal material from multiple Porites lutea corallites ($2 to 4 corallites). Nothdurft and Webb [2007] studied the microstructure and spatial variability of skeletal growth in four coral genera including Porites and they recommend caution is needed when microsampling that ''even a slight lateral divergence may invalidate the time series'' [see Nothdurft and Webb, 2007, Figure 17].…”
Section: Sampling Resolutionmentioning
confidence: 99%
“…In macro size axial coralite form a long rod also called as synapticulae. Contrary with massive coral that have solid structure of skeletal, branching Acropora has wider and sturdy, so this is the reason why Acroporid has faster growth rate than massive coral (Nothdurft and Webb, 2007).…”
Section: Growth Rate and Branch Of Acroporamentioning
confidence: 99%